Harnessing μ‐X‐Ray Fluorescence Spectroscopy as a Tool to Assess Extracellular Vesicle‐Induced Biomineralization - Mathieu Y. Brunet; Adam McGuinness; Kenny Man; Marie‐Christine Jones; Sophie C. Cox (Advanced NanoBiomed Research)
Bone cell‐derived extracellular vesicles (EVs) have been increasingly investigated as novel acellular strategies for bone regeneration due to their pro‐regenerative potency. The evaluation of such bone repair enhancement strategies commonly lies in the assessment of cell‐mediated mineral deposition, associated with destructive and nonhigh‐throughput methods. Herein, a robust methodology is presented to assess the osteogenic potential of an EV therapy using μ‐X‐ray fluorescence spectroscopy (μ‐XRF). Mineralizing osteoblast‐derived EVs (MO‐EVs) are isolated from conditioned media via ultracentrifugation and comprehensively characterized. Their pro‐osteogenic potency is validated via alkaline phosphatase activity, alizarin red, and picrosirius red staining for the evaluation of calcium and matrix deposition, respectively. μ‐XRF is first employed to quantify calcium and phosphorous levels as markers of minerals generating 2D elemental maps of the cultures. The in‐depth downstream analysis of the elemental maps reveals that MO‐EVs modulate mineralization in a time‐ and concentration‐dependent manner as MO‐EV concentration from 5 μg mL−1 significantly increases mineral coverage and increases calcium/phosphate levels in mineralized phases. Together, these results demonstrate the potential of μ‐XRF, allowing the examination of elemental levels, mineral coverage, and chemical phases in a single process and thus, offering a new platform for the therapeutic screening of osteogenic technologies with a resolution accommodating biological workflows.